A review of liners, bases and cements - Poran Samimi; Hamid Mazaheri; Vahid Alizadeh; Fahimeh Salamat; Sayed Mostafa Mosavinasab; Maryam Khoroushi (Isfahan University of Medical Sciences, 2011)
Introduction: Before placing or cementing a restoration into a cavity preparation, the clinician must decide whether a cavity base, liner or a protective cavity sealer should be placed. While this seems simple, the decision is complicated by an ever-increasing number of products available. In addition, the clinical success of an indirect restorative procedure depends, to a great extent, on the relationship between the restoration and the tooth. The practice of fixed prosthodontics has changed dramatically with the introduction of innovative techniques and materials. Adhesive resin systems are examples of these changes that have led to popularity of bonded ceramics and resin-retained fixed partial dentures. Materials and Methods: This review was collected with a scientific search in MEDLINE in relation to the following categories: the definition of liners, bases and cements, their clinical applications, mechanical properties, biocompatibility, principles of adhesion, specific types of materials and their use as liners, bases or cements. In addition, the review discusses cementation techniques for different types of restorations, and other relevant clinical information. Tables of products available and their properties are also presented.Conclusion: Although each cement type has been widely investigated, the correct clinical choice between them is not always clear. None of them is suitable to be used for the entire broad range of indirect restorative procedures. Therefore, their proper application requires a thorough understanding and awareness of each material's advantages and disadvantages, taking into account the restorative material, moisture control and preparation design (retentive or adhesive). Key words: Base, Cement, Dentin, Enamel, Liner.